Bioconversion of biodiesel-derived crude glycerol into lipids and carotenoids by an oleaginous red yeast Sporidiobolus pararoseus KM281507 in an airlift bioreactor - Manowattana A. (2017)
© 2017 The Society for Biotechnology, Japan. Here we tested the bioconversion of biodiesel-derived crude glycerol by the oleaginous red yeast Sporidiobolus pararoseus KM281507 in two bioreactors types (stirred-tank and airlift). High production yields (biomass, 10.62 ± 0.21 g/L; lipids, 3.26 ± 0.13 g/L; β-carotene, 30.64 ± 0.05 mg/L; total carotenoids, 46.59 ± 0.07 mg/L) were achieved in a 3.0 L airlift bioreactor under uncontrolled pH regimes (initial pH 5.63). Under optimized conditions (6.0 vvm aeration rate; 60 ± 5% constant dissolved oxygen [DO] maintained by flushing pure oxygen [O 2 ] into the vessel; 10,000 Lux light irradiation) volumetric production in the airlift bioreactor was further increased (biomass, 19.30 ± 1.07 g/L; lipids, 6.61 ± 0.04 g/L, β-carotene, 109.75 ± 0.21 mg/L; total carotenoids 151.00 ± 2.71 mg/L). Production was also recorded at a S. pararoseus KM281507 growth rate of 0.16 ± 0.00 h -1 (lipids, 0.94 ± 0.04 g/L/d; β-carotene, 15.68 ± 0.40 mg/L/d; total carotenoids, 21.56 ± 0.20 mg/L/d). Lipids from S. pararoseus KM281507 had a high unsaturated fatty acid content, with oleic acid (C18:1) accounting for 80% of all fatty acids. This high oleic acid content makes S. pararoseus KM281507 well-suited as a third generation biodiesel feedstock. Our findings show that airlift bioreactors are suitable for bioconversion of crude glycerol into lipids and carotenoids using S. pararoseus KM281507. This approach is advantageous because of its ease of operation, cost efficiency, and low energy consumption.